1964
DOI: 10.4141/cjps64-111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Postharvest Physiology and Storage Life of Pears

Abstract: Response of Anjou and Bartlett pears to nine storage temperatures ranging from 29° to 70°F was determined by periodic evaluation of ripened fruit, analysis of certain chemical and physical properties, and measurement of respiration throughout the storage period.After harvest, low metabolic activity persisted about 4 days in Bartlett and over 50 days in Anjou at 50° to 70°F. Anjou pears ripened only after a period of cold storage. The total amount of carbon dioxide respired during storage life diminished with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 0 publications
5
25
0
2
Order By: Relevance
“…A related observation is expression of cold response transcription factor, induced in tomato fruit by applied ethylene or, alternatively, by cold conditions (Zhao and others 2009). However, chilling‐induced acceleration of ripening in winter pears (Porritt 1964; Looney and others 1972) was accompanied by upsurge in ethylene evolution (Sfakiotakis and Dilley 1974) and emergence of ethylene biosynthesis transcripts (Lelievre and others 1997) suggesting that under cold conditions both cold shock and ethylene action combine to stimulate ripening in these fruit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A related observation is expression of cold response transcription factor, induced in tomato fruit by applied ethylene or, alternatively, by cold conditions (Zhao and others 2009). However, chilling‐induced acceleration of ripening in winter pears (Porritt 1964; Looney and others 1972) was accompanied by upsurge in ethylene evolution (Sfakiotakis and Dilley 1974) and emergence of ethylene biosynthesis transcripts (Lelievre and others 1997) suggesting that under cold conditions both cold shock and ethylene action combine to stimulate ripening in these fruit.…”
Section: Resultsmentioning
confidence: 99%
“…This perspective provides a conceptual frame work for interrelating and integrating previous observations. This view accounts for the stimulation of fruit ripening by environmental stress including drought stress (Littmann 1972), cold tress (Porritt 1964; Looney and others 1972; Mworia and others 2012), wounding stress (Starrett and Laties 1993), or nutritional stress (Knowles and others 2001). Similarly, acceleration of ripening in detached fruit including apple (Smock 1972), banana (Palmer 1970; George and Marriott 1985), grape (Coombe 1976) or avocado (Biale 1960; Burg 1962) might arise from water deficit resulting from disruption of water supply to fruit from the parent plant.…”
Section: Resultsmentioning
confidence: 99%
“…Some pear varieties have an absolute requirement for exposure to cold in order to produce ethylene and to induce ripening. This e †ect is evident in the late-keeping or "winterÏ types such as Anjou (Porritt 1964), Bosc (Sfakiotakis and Dilley 1974), Bartlett (Looney 1972) and Passe-Crassane (Leblond 1975 ;Morin et al 1985). Some pear varieties, such as Conference, which have no absolute requirement for cold storage to initiate ripening (Wilson et al 1990) seem to ripen much more rapidly after removal from storage at [ 1¡C than control fruit remaining at ambient temperature (Knee 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In other types of fruit such as apple and kiwi fruit, low temperatures hasten the induction of ethylene-synthesizing competency and homogeneous ripening (Pech et al, 1994). Although the effect of low storage temperatures on 'Bartlett' pear ripening has not been studied, Porritt (1964) reported that 'Bartlett' fruit harvested at late maturity with flesh firmness of 16.7 lb required 10 days at 70F or 13 days at 60F to soften to 3 lb if they had not been exposed to prior low storage temperatures. Flesh firmness of 'Bartlett' pears at optimum commercial maturity is between 19 and 17 lb (Porritt, 1964).…”
mentioning
confidence: 99%
“…Although the effect of low storage temperatures on 'Bartlett' pear ripening has not been studied, Porritt (1964) reported that 'Bartlett' fruit harvested at late maturity with flesh firmness of 16.7 lb required 10 days at 70F or 13 days at 60F to soften to 3 lb if they had not been exposed to prior low storage temperatures. Flesh firmness of 'Bartlett' pears at optimum commercial maturity is between 19 and 17 lb (Porritt, 1964). We frequently have observed that 'Bartlett' fruit harvested at optimum maturity do not ripen normally or they exhibit nonhomogeneous ripening at 68F if fruit have not been exposed to the low storage temperature at 30F or after <15 days of cold storage (personal observation).…”
mentioning
confidence: 99%